Empowerment of Women's Businesses through Catalog Digitalization for SMEs’ Products - Andriyastuti Suratman; Arief Darmawan; Muhammad Bakr Muhlison; Kartini Kartini; Murwanto Sigit; Syifaus Salsabila; Naya Nurfadillah; Novita Adiba Rahman (Asian Journal of Community Services, 2023)
This service initiated between the team and the Aisyiah Sleman Entrepreneurs Association in Yogyakarta (IPAS). The service focused on how to revitalize businesses that have been down due to the Covid-19 Pandemic with broader market access. Supporting digitalization insights and practices, entrepreneurs must collect service product data, and product visualizations to engage their potential market. The result is the increasing participants awareness the importance of digitally inventorying their products. Digitizing products in photos can help the MSME to expand their businesses and products closer to their respective potential markets. They also post products digitally so they have the product image in more detailed through social media such as Whats-App and Instagram.